Decomposição da liteira em igarapé sob floresta e área alterada na Amazônia Central – Brasil. - Paula, Joana D’Arc de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Allochthonous organic matter is the main source of energy for forest streams and leaf litter is the major component of the organic matter inputs to lotic systems. Taking this principle into account, the objective of the present work were: (1) to evaluate the decomposition rates of submersed foliar litter in two forest streams in central Amazonia, under different conditions (natural and managed), accompanying the carbon and nutrient concentrations in the litter, throughout the decomposition; and, (2) to evaluate the decomposition dynamics and the litter colonization by aquatic invertebrates in litter samples placed in the stream at three different distances from the pasture area, determining eventual differences between the invertebrate communities. Leaf litter species used in the experiments were: Siparuna bifida, Guatteriopsis sessiliflora, Henriettea cf. spruceana and Licania cf. laevigata. One treatment was the mixture of the four species, while other four treatments were the individual species placed within the litter bags. Two experiments were carried out using litter bags containing approximately 3 g each. The first experiment used 440 litter bags, which were placed in the at field from April to December, 2006 while the second experiment used 420 litter bags, from April to August, 2006. All litter species presented fast decomposition and the remaining dry weight in litter bags was different between leaf species (individual and mixed) and between the two forest streams. Species presented differences in the initial physical resistance, which were reflected in the weight losses at the end of the experiment. Nutrient release rates were positively correlated with the rates of dry weight losses. The density and richness of aquatic invertebrates found in litter bags also varied between species and distances from the pasture. Invertebrates belonging to the collector-gatherers group varied between distances from pasture and between leaf litter species both in density and in richness while the richness of predators varied only between litter species. Thus, the physical and chemical characteristics of each litter species, together with its distance to the pasture are determining rates and amounts of nutrient release to the forest stream. The invertebrates not only use the litter as a food and energy resource, but also as microhabitats. Then, litter plays an important role in the maintenance of the fauna of headwater forest streams, and the conversion of riparian vegetation into pastures would decrease the diversity of aquatic litter invertebrates, reducing the communities to the most resistant organisms.